Interactions between Foreign Investment Treaties and Customary International Law - Shokrani, Maziyar (Advances in Social Sciences Research Journal, 2019)
The increasing number of investment treaties raises the issue of relationship between these treaties and public international law. This paper investigated and argued that the substantive norms introduced in these treaties can contribute greatly to sources of public international law through State practice and opinio juris from one hand and customary international law can be applied to international investment disputes on the other hand.